Bauxite Mining in Africa Transnational Corporate Governance and Development - Knierzinger, Johannes (International Political Economy Series,, 2018)
This book deals with the consequences of the inclusion of African states and communities in the global aluminium chain. The so-called "New Scramble for Africa" of the 2000s illustrated how seriously African living conditions are affected by continuous cycles of boom and bust, and how strongly the quality of life currently depends on the investment decisions and corporate social responsibility policies of transnational corporations. Taking the example of the global production network of bauxite and aluminium, the author focuses on the socio-political aspects of this dependency, which he achieves through the conducting of a series of interviews with various involved parties.